Dexmedetomidine alleviates olfactory cognitive dysfunction by promoting neurogenesis in the subventricular zone of hypoxic-ischemic neonatal rats - Chen, Andi; Chen, Xiaohui; Deng, Jianhui; Wei, Jianjie; Qian, Haitao; Huang, Yongxin; Wu, Shuyan; Gao, Fei; Gong, Cansheng; Liao, Yanling; Zheng, Xiaochun (Frontiers in Pharmacology, 2022)
Background: Hypoxic-ischemic brain damage (HIBD) is the main cause of neurological dysfunction in neonates. Olfactory cognitive function is important for feeding, the ability to detect hazardous situations and social relationships. However, only a few studies have investigated olfactory cognitive dysfunction in neonates with HIBD; furthermore, the specific mechanisms involved have yet to be elucidated. It has been reported that neurogenesis in the subventricular zone (SVZ) is linked to olfactory cognitive function. Recently, dexmedetomidine (DEX) has been shown to provide neuroprotection in neonates following HIBD. In the present study, we investigated whether DEX could improve olfactory cognitive dysfunction in neonatal rats following HIBD and attempted to determine the underlying mechanisms. Methods: We induced HIBD in rats using the Rice–Vannucci model; DEX (25 µg/kg, i.p.) was administered immediately after the induction of HIBD. Next, we used triphenyl tetrazolium chloride (TTC) staining and the Zea-longa score to assess the success of modelling. The levels of BDNF, IL-1β and IL-6 were determined by western blotting. Immunofluorescence staining was used to detect microglial activation, microglial M1/M2 polarization and the extent of neurogenesis in the SVZ. To evaluate the olfactory cognitive function, the rats in each group were raised until post-natal days 28–35; then, we performed the buried food test and the olfactory memory test. Results: Analysis showed that HIBD induced significant brain infarction, neurological deficits, and olfactory cognitive dysfunction. Furthermore, we found that DEX treatment significantly improved olfactory cognitive dysfunction in rat pups with HIBD. DEX treatment also increased the number of newly formed neuroblasts (BrdU/DCX) and neurons (BrdU/NeuN) in the SVZ by increasing the expression of BDNF in rat pups with HIBD. Furthermore, analysis showed that the neurogenic effects of DEX were possibly related to the inhibition of inflammation and the promotion of M1 to M2 conversion in the microglia. Conclusion: Based on the present findings, DEX treatment could improve olfactory cognitive dysfunction in neonatal rats with HIBD by promoting neurogenesis in the SVZ by enhancing the expression of BDNF. It was possible associated that DEX inhibited neuroinflammation and promoted M1 to M2 conversion in the microglia.